The Prevalence of Mucormycosis in COVID-19 Patients - Dhruba Hari Chandi (Recent Updates in Disease and Health Research Vol. 9, 2024)
Unexpected occurrences that have occurred recently have made it more difficult for the current population to maintain a balance of livelihood. This is because of the COVID-19, but it has also brought with it several other uncommon and extremely deadly fungal infections, like mucormycosis, which lurk beneath the surface of the virus. Under the impact of COVID-19 Associated Mucormycosis, this infection causes a number of clinical disorders, the most frequent of which being rhino-cerebral illness. This condition occurs mainly in the patients with diabetes mellitus which can be extremely life threatening. Several other respiratory, gastrointestinal and cutaneous contaminations also occur during this condition. Numerous risk factors for mucormycosis exist and may coexist with the severity of the ailment. These include keto-acidosis in diabetic individuals, immunosuppressive medication users, history of pulmonary infections, and other nosocomial infections. There are no specific biomarkers available to diagnose Mucormycosis. Histopathological examination of the biopsied tissue and imaging of the involved area are most important in diagnosis. Being an anthropo invasive fungus, mucormycosis typically grows in areas with damp surfaces and decomposing and dead plant matter. Although they belong to a completely separate group, the dematiaceous fungi are referred to as "black fungus." Since the COVID-19 pandemic is on its massive widespread in the country, the new variant being more infectious, people are more tend to some other complications of the COVID-19 contamination such as that of the secondary fungal infections causing high mortality rates. The routine has to be followed by providing the patients with proper antifungal medications and the competence of a surgical expert alongside the operative facilities. A managed and equitable distribution of the resources for the COVID-19 support has to be managed in order to decrease the fatality rates of the patients.